Liberalized retail electricity markets: What we have learned after two decades of experience? - Poudineh, R (Oxford Institute for Energy Studies, 2019)
The retail electricity market, as the key link between end users and the wider electricity system, play a significant role throughout the power sector. This paper argues that the reference design of the retail market in the post liberalization era has not only failed to achieve its original objectives but has also proved to be unfit to keep pace with technological change, consumer preference, and the energy transition. Measures to reduce barriers to entry for new suppliers have distorted competition, put consumers at risk through unsustainable retail business models, and led to an unfair distribution of system and public policy costs. Lack of consumer engagement has been one of the biggest weaknesses of retail electricity markets. The nature of issues that impede engagement – such as complexity of the market and electricity tariffs, transaction costs, perceived barriers, and behavioural biases – have made remedial proposals, based on individual switching, less effective for the most disengaged consumers. The growth of government wedge and policy costs has reduced the size of the competitive portion of the retail tariff. At the same time, the structure of end users’ tariffs bears little relationship to the actual cost structure of the electricity system. This lowers the ability of retailers to recover these costs from energy consumption in an equitable manner. The emergence of non-traditional business models, the rise of new players, and a change in the nature of end users’ interactions with the electricity system call into question the dominance of the vertical architecture of an electricity market in which retail suppliers act as the hub. This paper concludes that retail market design and regulations need to be rethought to enable innovation and deliver the decarbonised, resilient, and affordable electricity that all consumers need.